Potentials of blockchain technology application in accounting and financial reporting - Tijana Matejić; Snežana Knežević; Aleksandar Joksimović; Stefan Milojević; Miljan Adamović (BizInfo)
Blockchain technology has caused a significant boom in academic and professional circles, becoming a central topic of discussion in the fields of business process modernisation, transparency, privacy, and data security. In the accounting field, this technology can bring revolutionary changes through the automation of record-keeping, the immutability of financial records, and the transparent exchange of data among all participants, thereby enhancing trust and efficiency in accounting practices. However, it also introduces challenges related to reduced employment opportunities in this profession and new skill requirements that the profession must adapt to. This paper discusses the characteristics of blockchain technology, its potential aspects and domains of application in accounting activities and financial reporting, the benefits and limitations of its implementation, and the changes it may bring to accounting practices and overall business operations. Additionally, the paper presents a conceptual system for the implementation of financial reporting and the automation of accounting activities through the application of smart contracts.